A Mixed Methods Study to Introduce Bioethics training in Undergraduate Medical Teaching of Community Medicine - Sarit Sharma; Mahesh Satija; Manvi Sagar; Anurag Chaudhary; Shruti Sharma; Pranjl Sharma (Medsci Publications, 2018)
Introduction: Bioethical principals are an integral part of medical practice. Young doctors face a lot of ethical dilemmas during their budding years highlighting the need for bioethics teaching during undergraduate period. The present study was done to evaluate the basic knowledge and attitude of MBBS students about bio- ethics and its inclusion in medical curriculum. Methods: Four week training in bioethics was provided to MBBS Final Prof Part-I students through lectures, group discussions, in- formative videos etc. For data collection, a pre-test and post-test proforma was filled by the students which was analysed by the investigators. Results: Statistically significant improvement was seen in knowl- edge regarding basics of bioethics. There was a clear improvement in the students' perception about importance of bioethics and atti- tude about following bioethics in clinical practice after the train- ing. Nearly half of the students agreed that bioethics should be taught throughout the MBBS curriculum. Conclusion: The study highlights the importance of introduction of bioethics training in curriculum of undergraduate students. Students in the study were willing to learn more and wanted this training to continue throughout MBBS course. Knowledge of bio- ethics will help these future doctors in dealing with routine ethical dilemmas.